The effects of brexpiprazole and aripiprazole on body weight as monotherapy in patients with schizophrenia and as adjunctive treatment in patients with major depressive disorder: an analysis of short-term and long-term studies. (September 2018) - Weiss, Catherine; Weiller, Emmanuelle; Baker, Ross A.; Duffy, Ruth A.; Gwin, Keva K.; Zhang, Peter; McQuade, Robert D.
Abstract : The aim of this analysis was to explore the effects of brexpiprazole and aripiprazole on body weight when used as monotherapy to treat schizophrenia and as adjunctive treatment to antidepressant treatment (ADT) for major depressive disorder (MDD) in short-term (4/6 weeks) and long-term (⩽52 weeks) studies. Body weight data were obtained from the clinical studies of each drug (brexpiprazole and aripiprazole), in schizophrenia and adjunctive treatment of MDD. Data were pooled and analyzed to assess the mean change in body weight and to determine the incidence of a clinically relevant change in body weight from baseline (≥7% increase or decrease, at any time) in each treatment group. The overall weight profiles for brexpiprazole and aripiprazole in the short-term and long-term treatment of schizophrenia, and MDD (adjunctive to ADT), were similar. In short-term schizophrenia studies, the mean weight increase was 1.2 kg for brexpiprazole and 0.6 kg for aripiprazole. In short-term MDD studies (adjunctive to ADT), the mean weight increase was 1.5 kg for brexpiprazole and 1.6 kg for aripiprazole. In the long-term schizophrenia studies, at week 52, the mean weight increase was 2.1 kg for brexpiprazole and 3.0 kg for aripiprazole. In long-term MDD studies (adjunctive to ADT), at week 52, the mean weight increase was 3.2 kg for brexpiprazole and 4.0 kg for aripiprazole. Clinically relevant increases or decreases in body weight were also similar for brexpiprazole and aripiprazole. Overall, in the treatment of schizophrenia, and in adjunctive treatment of MDD, brexpiprazole and aripiprazole have a similar effect on body weight over the course of 1 year. Abstract : Supplemental Digital Content is available in the text.